EFFECT OF SOLID DISPERSIONS ON THE SOLUBILITY OF METRONIDAZOLE - I. I. Krasnyuk (Jr.); S. R. Naryshkin; I. I. Krasnyuk; A. V. Belyatskaya; O. I. Stepanova; I. S. Bobrov; V. G. Yankova; J. V. Rau; A. N. Vorobiev (Фармация и фармакология (Пятигорск), 2021)
The aim of the work is to study the effect of solid dispersions using polyethylene glycols of various molecular weights on the solubility of metronidazole in water. Metronidazole is an antimicrobial and antiprotozoal drug. Its low solubility in water limits the use of metronidazole, causing technological difficulties and reducing its bioavailability. The solubility and release of the active substance from dosage forms can be increased using the solid dispersion methods. Solid dispersions are bi- or multicomponent systems consisting of an active substance and a carrier (a highly dispersed solid phase of the active substance or molecular-dispersed solid solutions) with a partial formation of complexes of variable compositions with the carrier material.Materials and methods. The substance of metronidazole used in the experiment, was manufactured by Hubei Hongyuan Pharmaceutical Technology Co., Ltd. (China). To obtain solid dispersions, polyethylene glycols of various molar masses – 1500, 2000 and 3000 g/mol – were used. The solid dispersions were prepared by “the solvent removal method”: metronidazole and the polymer were dissolved in a minimum volume of 96% ethyl alcohol (puriss. p.a./analytical grade) at 65±2°C, and then the solvent was evaporated under vacuum to the constant weight. A vacuum pump and a water bath were used at the temperature of 40±2°C. The dissolution of the samples was studied using a magnetic stirrer with heating, and a thermostatting device. The concentration of metronidazole was determined on a spectrophotometer using quartz cuvettes at the wavelength of 318±2 nm. To filter the solutions, syringe nozzles were used, the pores were 0.45 μm, the filter was nylon. Microcrystalloscopy was performed using a microscope with a digital camera. The optical properties of the solutions were investigated using a quartz cuvette and a mirror camera (the image exposure – 20 sec).Results. Obtaining solid dispersions increases the completeness and rate of the metronidazole dissolution. The solubility of metronidazole from solid dispersions increases by 14–17% in comparison with the original substance. The complex of physical-chemical methods of the analysis, including UV spectrophotometry, microcrystalloscopy and the study of the optical properties of the obtained solutions, makes it possible to suggest the following. The increase in the solubility of metronidazole from solid dispersions is explained by the loss of crystallinity and the formation of a solid solution of the active substance and the solubilizing effect of the polymer with the formation of colloidal solutions of metronidazole at subsequent dissolution of the solid dispersion in water.Conclusion. The preparation of solid dispersions with polyethylene glycols improves the dissolution of metronidazole in water. The results obtained are planned to be used in the development of rapidly dissolving solid dosage forms of metronidazole with an accelerated release and an increased bioavailability.